Analisa Nilai Perusahaan Ditinjau dari Profitabilitas dan Struktur Modal dengan Ukuran Perusahaan sebagai Variabel Intervening (Studi Empiris pada Perusahaan Subsektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2015 – 2018) - Joni, Joni; Hady, Hamdy; Elfiswandi, Elfiswandi (Jurusan PIPS FKIP UMMY Solok, 2020)
This reaserch was aimed to analyze the firm value in terms of profitability, capital structure and firm size partially and simultaneously on property and real estate companies listed on the Indonesia Stock Exchange in 2015 - 2018. The independent variables used in this study are profitability and capital structure; firm size as an intervening variable. While the dependent variable in this study is firm value. Firm value was calculated by using the Tobin'Q ratio. The total population in this research was 54 companies and 30 companies were taken as the sample. This research used secondary data that has passed the Classical Assumption Test. Hypothesis testing was carried out using Multiple Linear Analysis, Model test (t-test and F-Test), Coefficient Determination, and Path Analysis. The result of the research shows that :(1) Profitability partially has no effect on firm size ;(2) Capital structure partially has no effect on firm size ; (3) Profitability and capital structure simultaneously have no effect on firm size ;(4) Profitability partially has no effect on firm value ; (5) Capital structure partially has significant effect on firm value ;(6) Firm size partially has a significant effect on firm value ; (7) Profitability, capital structure and firm size simultaneously have significant effect on firm value : (8) Profitability has direct influence on firm value ;(9) Capital structure has direct influence on firm value.